Role of alveolar collapse in idiopathic pleuroparenchymal fibroelastosis - Kinoshita, Yoshiaki; Ishii, Hiroshi; Kushima, Hisako; Fujita, Masaki; Nabeshima, Kazuki; Watanabe, Kentaro (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Zonal aggregates of elastic fibres (zonal elastosis) and intraalveolar collagenosis with septal elastosis are histologic components of subpleural fibroelastosis of idiopathic pleuroparenchymal fibroelastosis (IPPFE). Zonal elastosis is considered to result from alveolar collapse, but this mechanism has not been fully justified. Methods: We immunohistochemically attempted to identify epithelial cells in zonal elastosis of 10 patients with IPPFE. The thickness of the zonal elastosis in relation to the total thickness of the fibroelastosis was examined to estimate the influence of zonal elastosis on the occurrence and development of IPPFE. Results: In 9 of the 10 patients, multi-cytokeratin-positive cells were found lining the inner surface of slit-like spaces embedded in the zonal elastosis. Zonal elastosis was predominant when fibroelastosis was < 1 mm thick but less predominant when it was ≥1 mm. Conclusion: The zonal elastosis was proven to result from alveolar collapse, which might be an initial lesion in IPPFE.